Development of an easy portable procedure for on-site determination of mercury and methylmercury. (16th April 2021) - Giacomino, Agnese; Ruo Redda, Andrea; Caligiuri, Rocco; Inaudi, Paolo; Squadrone, Stefania; Abete, Maria Cesarina; Abollino, Ornella; Morandi, Sara; Conca, Eleonora; Malandrino, Mery
Highlights: A portable procedure for determination of mercury and methylmercury is proposed. Anodic stripping voltammetry using a solid gold electrode is adopted. Home-made cartridges containing a new modified resin are adopted. Comparison between direct mercury analyser and voltammetry is made. Abstract: A portable measurement and speciation procedure for inorganic mercury (HgIN ) and methylmercury (CH3 Hg) was developed. A portable sample pretreatment was optimized to determine total mercury content. A new home-made sorbent (CYXAD, CHYPOS 101 modified Amberlite XAD), was prepared to separate HgIN and CH3 Hg. Mercury species were determined using square wave anodic stripping voltammetry (SW-ASV) with a solid gold electrode (SGE) and using a portable potentiostat. A certified reference material, five freeze-dried samples and three fresh samples were analysed with conventional voltammetric analyzer, after dissolution of the samples in microwave oven, and with a portable potentiostat after the mild eating procedure. The results obtained by SW-ASV were compared with those obtained using Direct Mercury Analyser (DMA). The quantification with the portable method is comparable to that obtained with the DMA. Retention tests showed the selectivity of CYXAD for HgIN, its stability and the possibility to re-use the same aliquot of resin.